Early life exposure to famine and reproductive aging among Chinese women. Issue 5 (May 2019) - Wang, Nengying; Huang, Yinqiong; Wen, Junping; Su, Qing; Huang, Yanling; Cai, Liangchun; Lin, Wei; Zong, Liyao; Huang, Huibin; Qian, Xiaofang; Zhu, Fengye; Sun, Han; et al.
Abstract: Objective: To assess the effect of early life exposure to famine, as endured during 1959 to 1961 in China, on reproductive aging in adult women. Methods: Between 2011 and 2012, 2, 868 women born around the Chinese famine period (1956-1964) were enrolled in this study from three communities in China. Age at natural menopause was obtained retrospectively from a structured questionnaire. The associations of early life famine exposure with reproductive aging during adulthood were estimated, with adjustment of socioeconomic status, lifestyle factors, and body mass index. Results: Women exposed to prenatal famine had a higher risk of early menopause (ie, natural menopause <45 years, odds ratio: 1.59, 95% confidence interval [CI]: 1.07, 2.36), and a nonsignificant trend of higher risk of premature ovarian failure (ie, natural menopause <40 y, odds ratio: 1.94, 95% CI: 0.93, 4.00), compared to unexposed women. Exposure to famine during childhood was not significantly associated with reproductive aging. In a secondary analysis focusing on the fetal exposure, prenatal famine exposure was associated with a higher risk of premature ovarian failure (odds ratio: 2.07, 95% CI: 1.08, 3.87), and a nonsignificant trend of higher risk of early menopause (odds ratio: 1.37, 95% CI: 0.98, 1.91), compared to those unexposed to prenatal famine. Conclusions: Our study showed that fetal exposure to famine was associated with an increased risk of early menopause. Such findings provided evidence in favor of the thrifty phenotype theory in reproductive aging and helped better understand the etiology of early menopause.